Peptidomic study on in vitro and in vivo phosphopeptide release during the chewing of gum fortified with a commercial casein hydrolysate. (April 2018) - Quarto, Maria; Nitride, Chiara; Ferranti, Pasquale; Mauriello, Rosalba; Garro, Giuseppina; Di Stasio, Michele; Volpe, Maria Grazia; Ferrazzano, Gianmaria Fabrizio; Chianese, Lina
Abstract: The kinetics of phosphopeptide release from gum fortified with a commercial casein hydrolysate in artificial and human saliva was studied. Using mass spectrometry techniques, the caseinophosphopeptide (CPP) composition of the commercial casein hydrolysate compared with a standard tryptic casein digest from whole raw cow milk was determined. In in vitro trials, the amount of CPPs released was always the same for each chewing time; in contrast, during in vivo chewing, a decrease of peptide levels was detected, from 10% after 5 min to 0.1% at 20 min, due to physiological swallowing. It is concluded that gums are a useful vehicle for CPP intake, owing to their functional role in bone health. However, their use is less satisfactory for prevention of dental caries, due to the brief contact with the enamel surface. Moreover, more calcium would need to be added to enrich the CPP fraction of the commercial hydrolysate.